2020
DOI: 10.1111/rda.13775
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9‐mediated MSTN disruption accelerates the growth of Chinese Bama pigs

Abstract: CRISPR/Cas9-mediated genome editing technology is a simple and highly efficient and specific genome modification approach with wide applications in the animal industry. CRISPR/Cas9-mediated genome editing combined with somatic cell nuclear transfer rapidly constructs gene-edited somatic cell-cloned pigs for the genetic improvement of traits or simulation of human diseases. Chinese Bama pigs are an excellent indigenous minipig breed from Bama County of China. Research on genome editing of Chinese Bama pigs is o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Subsequently, Rao et al used TALEN technology to successfully obtain MSTN gene-edited pigs and showed that the muscle bers of these pigs became thinner and more numerous, exhibiting the double-muscled phenotype in the hips (Rao et al, 2016). In 2020, Li et al and our group obtained MSTN-knockout miniature pigs and Bama minipigs, respectively (Li et al, 2020;Zhu et al, 2020b). Both breeds showed an increase in the number of muscle bers and a decrease in muscle ber size, indicating that the geneediting mediated MSTN-knockout signi cantly improved the meat production traits of pigs and increased their economic value.…”
Section: Genomic Off-target Identi Cationmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, Rao et al used TALEN technology to successfully obtain MSTN gene-edited pigs and showed that the muscle bers of these pigs became thinner and more numerous, exhibiting the double-muscled phenotype in the hips (Rao et al, 2016). In 2020, Li et al and our group obtained MSTN-knockout miniature pigs and Bama minipigs, respectively (Li et al, 2020;Zhu et al, 2020b). Both breeds showed an increase in the number of muscle bers and a decrease in muscle ber size, indicating that the geneediting mediated MSTN-knockout signi cantly improved the meat production traits of pigs and increased their economic value.…”
Section: Genomic Off-target Identi Cationmentioning
confidence: 99%
“…Although the application effect of the modi ed CBE tool on pigs might not be very high, in the practice of single-base editing of porcine cells, different editing targets could be compared, and the targets with higher relative activity could be selected for application. For example, in this study the four candidate targets were analyzed and compared to select the most active target and more e ciently prepare CBE-mediated single-base editing cells of Bama minipigs, thereby laying the foundation for the next step of producing single-base edited pigs through somatic cell cloning.In previous studies, MSTN-knockout was mainly achieved by CRISPR/Cas9-mediated random base insertion/deletion mutations leading to frameshift mutations(Li et al, 2020;Zhu et al, 2020b). Because the mutations are random and unpredictable, and CRISPR/Cas9 is prone to cause a series of adverse genomic consequences, there are many concerns about biosafety.…”
mentioning
confidence: 99%
“…Bama Xiang mini-pigs, an indigenous minipig breed from Bama Country of China, grow slowly and are lighter and fatter than the modern breeds such as Large White at slaughter, which makes them an ideal experimental animal model for biomedical research [ 22 , 23 ]. Notably, too-high fat content in skeletal muscle will greatly decrease the purchasing decisions of customers, thus decreasing the economic value of Bama Xiang mini-pigs [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…This gap necessitates further research to understand how it influences pork fat metabolism, IMF deposition and other meat quality traits. A study [ 101 ] shows that MSTN knockout using CRISPR/Cas9-mediated genome editing with subsequent somatic cell nuclear transfer offers a promising possibility for genetic improvement of economically important traits in pigs. Ren et al [ 79 ] demonstrated the active potential of MSTN in inhibiting the growth of muscles (double muscling) and acts via myogenic transcription factor 2C ( MEF2C ) which binds to the miR-222 promoter and suppress the translation of SCD5 to affect fat deposition [ 79 ].…”
Section: Genes Involved In Fat Metabolism and Imf Accretion In Pigsmentioning
confidence: 99%